2009
DOI: 10.1002/aic.12087
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and degradation of polyhydroxyalkanoate biopolymers in propylene carbonate

Abstract: New biobased materials and chemicals require different processing strategies than petroleum-derived commodities. The extraction and recovery of polyhydroxyalkanoate (PHA) biopolymers from the residual cellular biomass is particularly difficult because the polymer is accumulated within the cell. PHAs have low solubility in many classical polymer solvents and are most often dissolved using undesirable chlorinated solvents. The solubility kinetics is greatly diminished when these polymers are highly crystalline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
1
18
0
6
Order By: Relevance
“…Besides, 1,2-propylene carbonate is considered safe due to its low toxicity. It is widely used in many applications including cosmetics [24]. Fiorese et al [25] reported a maximum PHA yield of 95% and a purity of 84% when extracted from the C. necator cells at 130°C for 30 min without involving any pretreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, 1,2-propylene carbonate is considered safe due to its low toxicity. It is widely used in many applications including cosmetics [24]. Fiorese et al [25] reported a maximum PHA yield of 95% and a purity of 84% when extracted from the C. necator cells at 130°C for 30 min without involving any pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…In case of accidents, the potential release of a large amount of highly toxic and volatile solvents to the environment is also of great concern [17,[21][22][23]. Therefore, 1,2-propylene carbonate has been proposed as an alternative to halogenated solvents in the recovery process of PHA [24][25].…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, o uso de solventes tóxicos e altamente voláteis para a extração de P(3HB) (por exemplo, clorofórmio) é contraditório ao fato de que estes polímeros vêm sendo amplamente estudados para minimizar as agressões ambientais causadas pelos polímeros de origem petroquímica [7,15] . De acordo com Mcchalicher et al [16] , o solvente ideal para a extração de biopolímeros de microrganismos a pressões atmosféricas deve ser capaz de dissolver os PHAs abaixo da temperatura de degradação do polímero, minimizando a degradação da cadeia polímérica, ser reutilizável e apresentar baixos riscos ambientais. Neste contexto, a extração de P(3HB) com carbonato de propileno foi primeiramente proposta por Lafferty e Heinzle [17] , como alternativa aos solventes clorados.…”
Section: Introducãounclassified
“…Propylene carbonate (PC), segundo a IUPAC (International Union of Pure and Applied Chemistry), recebe a nomenclatura de 4-metil-1,3-dioxolan-2-ona, sendo um éster de ácido carbônico cíclico e apresenta propriedades interessantes como não persistir no meio ambiente porque é degradado e não é genotóxico, ou seja, não causa danos aos genes de uma célula ou de um organismo [18,19] . Embora haja preocupação sobre a presença de residuais provenientes dos solventes nos biopolímeros, o carbonato de propileno já foi aprovado para uso em aplicações sensíveis, tais como cosméticos e medicamentos [16] . Estudos têm demonstrado que o carbonato de propileno não é facilmente absorvido através da pele, podendo ser utilizado em uma variedade de cosméticos em concentrações de até 5% [18] .…”
Section: Introducãounclassified
“…Dentre os métodos de extração de P(3HB) abordados na literatura, os que fazem uso de solventes são os mais extensivamente utilizados. O carbonato de propileno (CP) é proposto como uma alternativa aos solventes halogenados nos processos de recuperação de P(3HB) (Mcchalicher et al, 2010), o seu elevado ponto de ebulição (240 °C) é uma vantagem, uma vez que, evita a evaporação e permite sua …”
unclassified